Differential regulation of insulin receptor substrates-1 and -2 (IRS-1 and IRS-2) and phosphatidylinositol 3-kinase isoforms in liver and muscle of the obese diabetic (ob/ob) mouse. - Nada J. Kerouz; Dieter Hörsch; Sebastian Pons; C. Ronald Kahn (The Journal of Clinical Investigation, 1997)
Intracellular insulin signaling involves a series of alternative and complementary pathways created by the multiple substrates of the insulin receptor (IRS) and the various isoforms of SH2 domain signaling molecules that can interact with these substrates. In this study, we have evaluated the roles of IRS-1 and IRS-2 in signaling to the phosphatidylinositol (PI) 3-kinase pathway in the ob/ob mouse, a model of the insulin resistance of obesity and non-insulin-dependent diabetes mellitus. We find that the levels of expression of both IRS-1 and IRS-2 are decreased approximately 50% in muscle, whereas in liver the decrease is significantly greater for IRS-2 (72%) than for IRS-1 (29%). This results in differential decreases in IRS-1 and IRS-2 phosphorylation, docking of the p85alpha regulatory subunit of PI 3-kinase, and activation of this enzyme in these two insulin target tissues. In ob/ob liver there is also a change in expression of the alternatively spliced isoforms of the regulatory subunits for PI 3-kinase that was detected at the protein and mRNA level. This resulted in a 45% decrease in the p85alpha form of PI 3-kinase, a ninefold increase in the AS53/p55alpha, and a twofold increase in p50alpha isoforms. Thus, there are multiple alterations in the early steps of insulin signaling in the ob/ob mouse, with differential regulation of IRS-1 and IRS-2, various PI 3-kinase regulatory isoforms, and a lack of compensation for the decrease in insulin signaling by any of the known alternative pathways at these levels.